Whose story is it? Mental health consumer and carer views on carer participation in research - Alyssa R. Morse; Owen Forbes; Bethany A. Jones; Amelia Gulliver; Michelle Banfield (Wiley, 2021)
Abstract Background Mental health carers contribute a unique set of perspectives and lived experiences to research; however, national research ethics guidelines do not specifically address the issues that affect informal carers as participants. Objective This study sought to explore Australian mental health consumer and carer views on the ethical conduct of research involving mental health carers. Design A public forum (n = 14; consumer = 5, carer = 9) and a subsequent series of interviews (n = 10; consumer = 5, carer = 4, both = 1) were conducted to investigate consumer and carer views on mental health research ethics. Data collection and analysis drew strongly on methodological features of grounded theory. Results Conducting research involving carers and consumer‐carer relationships raises potential concerns related to story ownership. Lived experience stories have shared and separate elements; thus, it is important to consider potential risks to the privacy of non‐participants and of social harm to participants' relationships when conducting research in this space. These risks could be minimized and managed through communication between researchers and participants, and within relationships. Conclusions When conducting research involving carers and consumer‐carer relationships, researchers may need to facilitate the negotiation of information‐sharing boundaries within relationships and the safe and confidential telling of shared stories.